Nonlinear fluid-structure interaction for multi-dimensional seismic analyses of liquid storage tanks - Özdemir, Zühal. (Thesis (Ph.D.)-Bogazici University.Kandilli Observatory and Earthquake Research Institute, 2009., 2009)
Real nonlinear behavior of liquid storage tanks includes many complexities which are caused by material yielding, large amplitude free-surface sloshing, non-linear fluid structure interaction, high deformations of tank base and shell, out-off round distortions of the tank shell, soil-tank interaction, successive separation and contact between tank base and foundation and plastic rotations of tank base plate. These nonlinear behavior mechanisms result in different failure modes such as buckling at the tank shell (elephant foot buckling or diamond shape buckling), separation of the junction between the base plate and tank wall due to high joint stresses, uneven settlements at the tank base and rupture of the anchors. The algorithm to be employed for the seismic analyses of tanks should account for these nonlinearity effects for the accurate description of the performance of tanks during earthquakes. In this thesis, fluid-structure interaction algorithm of finite element method which can take into account the effects of geometric and material nonlinearities of the tank and nonlinear sloshing behavior of contained liquid is utilized to evaluate the actual behavior of steel cylindrical ground supported liquid storage tanks when subjected to realistic base motions. Since seismic design codes generally define ground shaking in the form of an acceleration response spectrum, earthquake ground motions is selected and processed using spectrum matching techniques in time domain to be compatible with the Turkish Seismic Design Code (2007) spectra. In addition to two horizontal components of ground motion, the vertical component is also taken into account in order to determine relative importance of vertical ground motion on the behaviors of anchored and unanchored tanks. In order to clarify the key question of tank problems whether anchoring would prevent earthquake damage to the tank, numerical analyses are carried out on the same tank model having two different support conditions: anchored and unanchored. The consistency of the provisions presented in current tank seismic design codes and finite element method analysis results are evaluated and recommendations on seismic tank design codes are presented.
Keywords: Storage tanks -- Earthquake effects.